The Impact of Mobile Learning Utilization on Students' Critical Thinking Skills in the Regional Geography Course - Dhohirrobbi, Achmad; Nafsi, Bella Izzatun; Shobah, Wulan Nurus; Firmantika, Lusty (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3176, 2024)
The effect of mobile learning on improving students' analytical thinking in the Indonesian Regional Geography course at the Department of Social Studies Education, UIN Maulana Malik Ibrahim Malang. The research uses a quasi-experimental method with a quantitative approach. The subjects of the study consisted of 60 students, divided into two groups: a control group and an experimental group. The instruments used were pretests and posttests, each consisting of 18 multiple-choice questions based on critical thinking indicators. Validity and reliability tests showed that the instruments were reliable. The data were analyzed using normality tests, homogeneity tests, and paired sample t-tests with a significance level of 5%. The results of the study indicate that the use of mobile learning has a significant positive impact on enhancing students' critical thinking skills, with a significance value less than 0.05. These findings are consistent with previous research, which shows that mobile-based learning technologies are effective in improving students' critical thinking skills and learning outcomes. Therefore, the development of mobile learning is expected to improve the quality of Regional Geography education and address the limitations of current learning media.